IFPA meeting 2018 workshop report I: Reproduction and placentation among ocean-living species; placental imaging; epigenetics and extracellular vesicles in pregnancy. (1st September 2019) - Acharya, Ganesh; Bartolomei, Marisa; Carter, Anthony M.; Chamley, Larry; Cotton, Charles F.; Hasegawa, Junichi; Hasegawa, Yuri; Hayakawa, Satoshi; Kawaguchi, Mari; Konwar, Chaini; Magawa, Shoichi; Miura, Kiyonori; et al.
Abstract: Workshops are an important part of the IFPA annual meeting as they allow for discussion of specialized topics. At IFPA meeting 2018 there were nine themed workshops, four of which are summarized in this report. These workshops discussed new knowledge and technological innovations in the following areas of research: 1) viviparity in ocean-living species; 2) placental imaging; 3) epigenetics; and 4) extracellular vesicles in pregnancy. Highlights: Evolution of matrotrophy, with and without a placenta, studied in ocean-going species. Standardizing protocols is essential for use of placental imaging for screening and diagnostic purposes. Placental methylation differences between groups is influenced by differences in population structure. Exosomal signaling represents an essential pathway mediating intercellular communication.